Penggunaan Aplikasi Kahoot Sebagai Media Dalam Meningkatkan Hasil Belajar IPS Kelas VI SD - Pratiwi, Ike; Hidayati, Fifin; Saroi, Umi; Lanovianti, Yeni Novita; Zulfiati, Heri Maria (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research is motivated by the fact that there are still many students who are bored and less interested in learning social studies. This is the basis for the need for innovative learning media so that students are interested and enthusiastic when studying social studies. The aim of this research is to determine the improvement in social studies learning outcomes in elementary schools and how to use Kahoot media in social studies learning. The research carried out was Classroom Action Research (PTK). Data collection using test and observation methods. The results of this research show that there is an increase in the average learning outcomes from 77 in cycle I and cycle II of 83. Apart from that, the research results show that children are happier and more enthusiastic in learning social studies, this can be seen from the students' enthusiasm in solving questions using Kahoot. Based on this data, it can be concluded that the Kahoot game can improve social studies learning outcomes regarding getting to know Asean countries for class VI students at SD Negeri Berbah 2 Sleman.